Nilai-Nilai Spiritual Kebudayaan Macan Putih: (Studi Deskriptif Nilai-nilai Spiritual Kebudayaa Macan Putih di Masyarakat Desa Warungkandang, Kecamatan Plered Kabupaten Purwakarta) - Deni Miharja; Ahmad Saepudin (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2017)
White tiger culture is a culture that is often done most of society that were previously generated from a form of culture, and one of the seven elements of culture that exist in Sundanese. The known culture on today's society in the area of art and culture is Palered Paleredan. Cultural arts paleredan called with martial arts/pencaksilat community perpetrated by plered either from start of school age at the junior level, HIGH SCHOOL level to the youth and the elderly.Culture of white Tigers have a historically derived from the Sundanese order resulting from copyright, taste, karsa initiated from the seven elements of culture that is art and culture in sunda. White Tiger from college Bantam carried by people travelling to Bandung, and then Plered Purwakarta. As for the spiritual values which are often dipraktikan is of some elements and aspects of animism, dynamism and monotaisme can even be described as a syncretism between the culture with Islamic religious. This can be inferred between the practice of the White Tiger sambat by having an item lapadz Asma'ul Husna, with the belief that it is already at benchmark to a belief which is exactly on the Esaan God and on one side of the movement is performed at the time of the movement under way should provide offerings in the form; raw meat, raw egg, black coffee and cigarette gudang garam merah, to bring forth the will in appropriate hodam sambat by the offender, it is for the sake of presenting supernatural beings into the body.